3D Printing Improve the Effectiveness of Fracture Teaching and Medical Learning: A Comprehensive Scientometric Assessment and Future Perspectives - Shi, Jian; Fu, Shenao; Cavagnaro, María José; Xu, Shaokang; Zhao, Mingyi (Frontiers in Physiology, 2021)
Fractures of complex body parts are often serious and difficult to handle, and they have high technical and training requirements. But the realistic situation is, there are few opportunities for the junior residents, trainee doctors and especially medical students to contact with enough clinical practice and see such fracture patients. Fortunately, with the rapid development and continuous progress of three-dimensional (3D) printing and related technologies, this situation has gradually gotten better and better. In this research, we confirmed that 3D printing technology can improve the effectiveness in fracture teaching and medical learning from multiple dimensions. We comprehensively screened and assessed 223 papers from the Web of Science (WoS) Core Collection on October 3, 2021 with “((3D) AND ((printing) OR (printed)) AND (fracture)) AND ((education) OR (training) OR (teaching))” as the retrieval strategy. And we used the VOSviewer software to analyze the keywords and countries and the organizations of the publications, then a series of scientometric and visualized analysis were made based on the retrieval results. Next multiple databases were retrieved according to our selection criteria, we selected eight studies for the extensive literature analysis. The extracted data contains information of authors, problems solved, participants, methods, assessments, results and benefits/limitations. These intuitive and in depth analysis further confirmed and appraised the advantages of 3D printing in complex fracture models more objectively. In conclusion, 3D printing can improve the effectiveness and extension of fracture teaching as well as medical learning by providing the powerful interaction with 3D effect, wakening students learning interest and allowing the junior residents, trainee doctors to have as realistic a virtual practice experience as possible. By this research it is expected that more researchers could be attracted to conduct more comprehensive and thorough studies on the application of 3D printing for training and educational propose, to promote the development of 3D technology-based medical education practice and further deepen the reform of medical education and improve the quality of fracture education and learning.